A Lesson Design on the Subject of Religion as a Course Unit in Language Teaching - Coşkun, Hasan (Journal of Education Culture and Society, 2022)
Aim. The purpose of this qualitative research is the preparation, implementation and evaluation of a sample lesson focused on the selection of the subject of religion for the German courses taught in universities. The second purpose of this research is to contribute to international understanding between peoples with different religious beliefs. Methods. This research pertaining to religion is qualitative in nature. In this research, the document analysis technique was used. The research on the subject of religion was taken up during the 2021/2022 academic year in my selective German courses at the Hacettepe University. Results. The successful contribution of the lesson planning model mentioned in this article was also observed in the teaching activities in primary and secondary schools conducted earlier. It was also seen that the students who attended the German courses in connection with education or work in Europe. Conclusions. It was observed that the participants talked about Islam, Christianity, Judaism, Buddhism and Hinduism. It is important to remark that the interest of the participants in German lessons still continues. Therefore, effective lesson planning models and unique methods should be further developed. Originality. German language courses are offered as a foreign language learning practice in Turkish schools, private institutions and universities as elective foreign language courses. Students from all the departments of the university may attend the elective German language classes. To conduct the German courses effectively, a suitable method should be developed which will help the participants who come from different countries and students with different levels of fluency.